The Highlights of the Annual Students and Young Scholars Conference on Translation “TELL ME MORE 2025” - Mongird, Beata; Volgina, Victoria (Respectus Philologicus, 2025)
The international conference for young scholars on translation TELL ME MORE was held for the third consecutive year at Vilnius University, Kaunas Faculty on May 7th, 2025. This annual event brought together students and emerging scholars from various Lithuanian and European universities for an intensive day of scholarly exchange and insightful discussions. Providing a platform for exploring various facets of translation and fostering interdisciplinary research, the conference received diverse submissions. The topics included: audiovisual translation and accessibility; literary translation; localisation and technical translation; multimodal and AI-related translation research; intersemiotic translation and adaptation. A particular emphasis was placed on accessibility, highlighted by a guest speaker from Lithuanian Audiosensory Library. The paper critically reviews four parallel conference sessions, providing key insights into the presented studies.